2005
DOI: 10.2514/1.10275
|View full text |Cite
|
Sign up to set email alerts
|

Damage Tolerance and Fail Safety of Welded Aircraft Wing Panels

Abstract: An investigation is presented on fatigue crack growth behavior and fail safety of integral stringer panels typified by welded aircraft fabrications. The stringer panel is made of aluminum alloy 2024-T351 and fabricated by the variable-polarity plasma-arc welding process. The sample simulates a part of the lower-wing skin structures. Based on the linear elastic fracture mechanics, numerical simulations are performed for two configurations, two-stringer and nine-stringer panels, and three damage scenarios, in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…Recently a new concept of using bonded structures to enhance the damage tolerance of aircraft structures ab initio has been introduced and studied [159][160][161]. The article by Zhang and Irving in this special issue [162] provides additional information on analysis approaches for damage tolerance assessments for structures with bonds or stiffeners.…”
Section: Specific Problems Of Bonded Structuresmentioning
confidence: 99%
“…Recently a new concept of using bonded structures to enhance the damage tolerance of aircraft structures ab initio has been introduced and studied [159][160][161]. The article by Zhang and Irving in this special issue [162] provides additional information on analysis approaches for damage tolerance assessments for structures with bonds or stiffeners.…”
Section: Specific Problems Of Bonded Structuresmentioning
confidence: 99%
“…What is more, Bushnell and Rankin [3] demonstrated that including small sub-stiffeners between the conventional primary stiffeners 'can not only lead to an increased buckling resistance, but more importantly to a much more robust optimum in terms of stiffener pitch'. Additionally, the damage tolerance characteristics of stiffener panel structures may be improved by the addition of plate element features designed to retard fatigue crack growth [4][5][6][7]. Considering panel post-buckling, improved plate stability should translate into improved collapse performance.…”
Section: Introductionmentioning
confidence: 99%
“…Integrally machined processes produces a high scrap rate of expensive aluminium alloys which results in a high manufacturing cost. Structures produced by mechanical fastening have to rely on numerous riveted and bolted joints which are potential failure locations due to a higher stress concentration factor associated with fastener holes [1]. In order to improve the damage tolerance and avoid large penalising safety factors, selective reinforcement such as novel crack retarding features can be incorporated into critical locations within the structure.…”
Section: Introductionmentioning
confidence: 99%